Constitutional change and security forces in Southeast Asia: Lessons from Thailand and Myanmar - Paul Chambers (2018)
Achieving civilian control of security forces through constitutional reform processes has been a major challenge for young democracies or democratizing countries in Southeast Asia. In many cases, governments seeking to establish or consolidate civilian control have been faced with coups d'état or the threat of coups. The successful enshrinement of laws reining in security force adventurism has often accompanied compromises which at most provide militaries with considerable latitude in their areas of decision-making or at least protect soldiers from judicial prosecution. Ultimately, the constitutional incorporation of security forces into embedded political life is no easy task. This article examines two country cases of "defective" democracies. In each case, security forces have moved towards becoming more integrated under the constitutions of civilian-led regimes. This study poses four questions. First, how did the institutionalization of security forces under civilian-led constitutions occur? Second, how did these experiences vary? Third, to what extent do these security forces today possess differing degrees of enshrined powers? And fourth, based upon these experiences, how might civilian control be sustained over time? The article argues that constitutional change acceded to by security forces more often than not results from informal bargaining and concessions by civilians. However, the initial bargain can later transform itself towards more or less security force interventionism depending upon three variables: the heritage of authoritarianism; the relative unity of civilians as opposed to the security forces; and threat environments. © 2014 ISEAS.